Analisis Pekerjaan dan Dukungan Keluarga terhadap Cakupan Imunisasi Rutin Lengkap Bayi dan Balita pada Kelurahan Juata Laut - Nurtilawati, Sri; Wahyudi, Donny Tri; Alfianur, Alfianur; Handayani, Fitriya; Zulfia, Rahmatuz; Ose, Maria Imaculata (Universitas Malahayati, 2024)
ABSTRACT Immunization services are one of the most effective and efficient efforts to prevent and break the chain of communicable diseases. According to data from the Local Area Monitoring of the Juata Health Center, Juata Laut Village has not yet reached UCI (Universal Child Immunization), which is 56.4%, while the UCI target is 95%. This study aims to determine the relationship between employment status and family support on Complete Routine Immunization Coverage for Infants and Under-fives in Juata Laut Village. This research is a quantitative analytic study with a cross sectional design. The sample consisted of 50 mothers who had children aged less than 2 years with complete and incomplete routine immunizations obtained from total sampling. Data analysis used univariate and bivariate analysis with Chi Square test. The results showed that the mother's employment status was closely related to the achievement of complete routine immunization coverage for children under two with p-value = 0.001 < α (0.05) and there was a significant relationship between family support and the complete routine immunization status of infants and under-fives in Juata Village. Sea with p-value = 0.001. The conclusion of this study is that the mother's employment status and family support are related to complete routine immunization coverage for infants and under-fives in Juata Laut Village. To Health Center staff further improve health promotion by providing counseling on the importance of Complete Routine Immunization for infants and Bad and old, the side effects of the benefits of immunization. The community is expected to be more active in participating in the implementation of immunization. Keywords: Complete Routine Immunization, Coverage, Infants, and Under-Fives ABSTRAK Pelayanan imunisasi merupakan salah satu upaya yang paling efektif dan efisien untuk mencegah dan memutus mata rantai penyakit menular. Menurut Data dari Pemantauan Wilayah Setempat Puskesmas Juata bahwa Kelurahan Juata Laut belum mencapai UCI (Universal Child Immunization) yaitu 56,4% sedangkan target UCI 95%. Penelitian ini bertujuan untuk mengetahui hubungan status pekerjaan dan dukungan keluarga terhadap Cakupan Imunisasi Rutin Lengkap pada Bayi dan Baduta di Kelurahan Juata Laut. Penelitian ini merupakan penelitian kuantitatif analitik dengan desain cross sectional. Sampel terdiri dari 50 ibu yang memiliki anak usia kurang dari 2 tahun dengan imunisasi rutin lengkap dan tidak lengkap yang didapatkan dari total sampling, analisis data menggunakan analisis univariat dan bivariat dengan uji Chi Square , α: 0,05. Hasil penelitian menunjukkan bahwa status pekerjaan ibu berhubungan erat dengan pencapaian cakupan imunisasi rutin lengkap bagi anak baduta dengan p-value =0,001 dan terdapat hubungan signifikan antara dukungan keluarga terhadap status kelengkapan imunisasi rutin lengkap bayi dan baduta di Kelurahan Juata Laut dengan p-value= 0,001. Kesimpulan dari penelitian ini adalah status pekerjaan ibu dan dukungan keluarga berhubungan dengan cakupan imunisasi rutin lengkap pada bayi dan baduta di Kelurahan Juata Laut. Kepada Petugas Puskesmas lebih meningkatkan promosi Kesehatan dengan memberikan penyuluhan pentingnya Imunisasi Rutin Lengkap bagi bayi dan Baduta, efek samping keuntungan pemberian imunisasi. Masyarakat diharapkan dapat lebih aktif berperan serta dalam pelaksanaan imunisasi. Kata Kunci: Baduta, Bayi, Cakupan, dan Imunisasi Rutin Lengkap, Cakupan